ANALISIS IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: STUDI LITERATUR TERHADAP TANTANGAN DAN PELUANG - Zakia Indana Zulfa; Akhmad Syahri; Musta’in (cendekia citra gemilang, 2026)
This study aims to analyze the implementation of the Merdeka Curriculum in Islamic Religious Education (PAI), with a focus on the challenges and opportunities that emerge in educational practice. The phenomenon under investigation relates to the gap between the conceptual framework of the Merdeka Curriculum, which emphasizes student-centered learning, and the reality of PAI instruction, which still tends to be normative and traditional. This research employs a qualitative approach using a library research design. Data were collected through documentation techniques by examining various scholarly sources, including indexed journal articles, academic books, and relevant official documents, particularly those published within the last 5–10 years. The data sources were selected based on their credibility and relevance to the research topic. Data analysis was conducted using content analysis techniques, involving stages of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the Merdeka Curriculum in PAI has shifted toward the use of project-based learning, student-centered learning, and the strengthening of the Pancasila Student Profile. However, several major challenges remain, including teachers’ limited understanding of the curriculum, the persistence of traditional teaching methods, and inadequate educational facilities and infrastructure. On the other hand, the identified opportunities include increased student learning independence, more contextualized learning, innovation in teaching methods, and the strengthening of religious character. These findings contribute to enriching the theoretical discourse on the integration of the Merdeka Curriculum in PAI and provide practical implications for improving teacher competence and educational policy. Future research is recommended to conduct empirical studies across various educational contexts to validate further and expand these findings.